NEEDS ANALYSIS OF ACADEMIC ENGLISH SKILLS AMONG ETHIOPIAN POLICE UNIVERSITY STUDENTS - Geremew Garda Wozie (Universitas Islam Sumatera Utara (UISU), 2026)
This study investigates the academic English language needs of first-year students at the Ethiopian Police University (EPU), aiming to inform the design of a discipline-sensitive English for Academic Purposes (EAP) curriculum. English functions as the medium of instruction at EPU. However, many students experience difficulties with the academic literacy skills essential for success in policing, law enforcement, and criminal justice education. The study employed a mixed-methods research design grounded in English for Specific Purposes (ESP), EAP, and Needs Analysis (NA) frameworks. Data were collected through questionnaires administered to 200 students and 30 instructors, as well as semi-structured interviews with selected 10 students and five teachers. Quantitative data were analyzed using descriptive statistics, while qualitative data were examined through thematic analysis to identify patterns in perceived academic language challenges and required competencies. The findings indicate that six core skills—listening, speaking, reading, writing, grammar, and vocabulary—emerged as critical for academic success. The analysis also revealed perception gaps between teacher emphasis on academic reading and writing and student prioritization of oral communication. These results highlight a misalignment between institutional expectations for advanced academic literacy and students’ current proficiency levels. Based on the findings, the study recommends the development of a structured, needs-based EAP curriculum that strengthens academic literacy, enhances student performance, and aligns language instruction with the disciplinary demands of policing and criminal justice education.